PVALB: análise do efeito da expressão ectópica em linhagens de carcinoma da tiroide - Mendes, Thais Biude [UNIFESP] (2016)
Our group identified a panel of molecular markers (C1orf24, ITM1 and PVALB) that can accurately distinguish between benign and malignant thyroid lesions. Despite the fact that the identification of these new markers may ultimately help patient care, the current understanding of their biological functions remains largely unknown. PVALB stains specifically the benign Hürthle cell adenoma (HCA), while tests negative in a wider variety of thyroid carcinomas including Hürthle cell carcinoma (HCC). As its expression is lost during tumor progression, in this study we ectopically expressed PVALB in two thyroid carcinoma cell lines (FTC-133 and WRO) and dissected the mechanism underlying the phenotypic changes commonly observed in Hürthle cell tumors. We demonstrated that PVALB sequesters free cytoplasmic Ca2+, which ultimately lowers calcium levels and precludes endoplasmic reticulum (ER) Ca2+ refilling, therefore, inducing ER stress through PERK signaling, as well as compromising the flow of Ca2+ into the mitochondria. By investigating mitochondrial morphology and membrane potential, we demonstrated that PVALB promotes an increase in mitochondrial mass and cell size, in parallel with changes in mitochondrial morphology. Furthermore, PVALB ectopic expression diminished cell proliferation rate and induced cell death through the AKT/GSK-3? pathway. We further demonstrated by immunohistochemistry that PVALB expression colocalizes with the presence of Ca2+ in HCA samples and, therefore, our in vitro results show striking similarities with the results obtained from the analysis performed in Hürthle tumors sections. In summary, PVALB plays a role in cellular calcium homeostasis, ER stress and cell death, most likely related to its role in mitochondrial dynamics. These data support the hypothesis that the loss of PVALB plays a role in the progression of thyroid tumors, predominantly in HCC, and therefore, it may act as a tumor suppressor gene.